The impact evaluation of soil liquefaction on low-rise building in the Meinong earthquake - Chih-Chieh Lu; Jin-Hung Hwang; Shang-Yi Hsu (Earth, Planets and Space, 2017)
Abstract This paper presents major preliminary observations on the liquefaction-induced damages in the Meinong earthquake (M L = 6.4). The severe damages to buildings centered on Huian and Sanmin Streets in Tainan City where the places were reclaimed fish or farm ponds with poor construction quality from many decades ago. To better understand the effect due to the soil liquefaction at these sites, the information provided by the in situ 13 Standard Penetration Test boreholes and 5 Cone Penetration Test soundings accompanying with the PGAs derived from the near seismographs was used to conduct the soil liquefaction evaluation by the Seed method (Seed et al. in J Geotech Eng ASCE 111(12):1425–1445, 1985) when subject to the Meinong earthquake. The liquefaction potential index (LPI) was then evaluated accordingly. From the results, it was found that the estimated damage severity was not consistent to the field conditions if the local site effect was not taken into account. To better reflect the site response in such sites, the sites’ PGAs in the PGA contour map were multiplied by 1.5 times to quantify the amplification effects due to the soft geological condition. In addition, the PGAs based on other simple approaches were evaluated as well for comparison. Besides, the effects of fines content and magnitude scaling factor were also discussed in this paper. After that, several common simplified methods were also used to calculate the LPI when subject to the Meinong earthquake in order to evaluate the applicability of these simplified methods.